New problems of a new health system: the creation of a national public policy of rare diseases care in Brazil (1990s-2010s) - Luiz Alves Araújo Neto; Luiz Antonio Teixeira (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2020)
This study discusses actors and institution movements leading to the disclosure in 2014 of Resolution 199 by the Brazilian Ministry of Health, which establishes the National Policy for the Comprehensive Care of Persons with Rare Diseases. Taking as sources the mainstream newspapers, drafts law, and secondary literature on the subject, we begin our analysis in the early 1990s when the first patient associations were created in Brazil - mainly for claiming more funds for research on genetic diseases - and arrive at the late 2010s when negotiations for a national policy are taking place in the National Congress. Resolution 199 is part of an ongoing process and the path towards its disclosure and the complications that followed have given us elements to discuss contemporary aspects of the Brazilian public health. Based on the references of the history of the present time and the social studies of science, we argue that two aspects have been fundamental to creating a national policy: framing different illnesses within the terminology "rare diseases" and the construction of a public perception about the right of health which is guaranteed by the 1988 Brazilian Constitution.